ACCEPTABILITY TEST OF PROCESSED TUBER PRODUCTS AS A LOCAL FOOD ALTERNATIVE - Siti Nurlani Harahap; Fitri Dian Nila Sari; Riani Sari Sembiring (Adisam Publisher, 2026)
The purpose of this study is to determine the level of acceptance of panellists towards processed sweet potato–potato patties and purple sweet potato onde-onde through organoleptic tests. This research is an experiment with a completely randomized design (CRD) involving 15 trained panelists from the academic community of Nahdlatul Ulama University of North Sumatra. The research method includes product development with various formulations, followed by a hedonic test on the attributes of taste, color, aroma, and texture using a numerical scale of 1–5. The data from the panelists' evaluations were analyzed descriptively to determine the most preferred treatment. Research results show that for perkedel products, formulation P0 (100% sweet potato, 0% potato) obtained the highest scores in all organoleptic attributes (taste 3.53; color 3.67; aroma 3.47; texture 3.67), making it the formulation most preferred by the panelists. In purple sweet potato onde-onde products, the most preferred taste attribute was found in treatment M2 (50% glutinous rice flour, 50% purple sweet potato) and M4 (100% purple sweet potato), whereas the best color, aroma, and texture were obtained in treatment M3 (25% glutinous rice flour, 75% purple sweet potato). The use of yellow sweet potatoes in full produces fritters with the best sensory quality, Meanwhile, the substitution of purple sweet potato in a balanced or dominant proportion can increase panelists' acceptance of onde-onde.